2014
DOI: 10.5664/jcsm.3960
|View full text |Cite
|
Sign up to set email alerts
|

Home-based Diagnosis of Obstructive Sleep Apnea in an Urban Population

Abstract: understand patient preferences with respect to setting of testing; home vs. in-laboratory. METHODS ParticipantsAdult African Americans, age ≥ 18 years at a single tertiary care center, with high risk for OSA (defi ned by the Berlin Questionnaire, n = 75) were recruited. The Berlin Questionnaire asks about snoring, daytime symptoms, high blood pressure, and body mass index (BMI).9 A positive response in 2 of 3 categories of questions is indicative of high risk for OSA and determined eligibility for enrollment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…When two studies evaluated the home-based PAT device against in-laboratory PSG at an AHI cutoff of ≥ 15, specificity ranged from 0.77 to 1.00 and sensitivity ranged from 0.92 to 0.96. 105,106 A single study evaluated the PAT device at an AHI cutoff of ≥ 30, and reported a specificity of 0.82 (95% CI: 0.57 to 0.96) and sensitivity of 0.92 (95% CI: 0.62 to 1.00) 105 (see supplemental material, Table S55 through Table S57). …”
Section: Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…When two studies evaluated the home-based PAT device against in-laboratory PSG at an AHI cutoff of ≥ 15, specificity ranged from 0.77 to 1.00 and sensitivity ranged from 0.92 to 0.96. 105,106 A single study evaluated the PAT device at an AHI cutoff of ≥ 30, and reported a specificity of 0.82 (95% CI: 0.57 to 0.96) and sensitivity of 0.92 (95% CI: 0.62 to 1.00) 105 (see supplemental material, Table S55 through Table S57). …”
Section: Accuracymentioning
confidence: 99%
“…104 Two cross-over studies randomized patients to home-based PAT, and in-laboratory simultaneous PSG and PAT. 105,106 For comparison to in-laboratory PSG, only the home-based PAT data were used for this recommendation. A single study that evaluated the performance of the PAT device in the home against in-laboratory PSG using a cutoff of AHI ≥ 5, 106 reported a specificity of 0.43 (95% CI: 0.22 to 0.66).…”
Section: Accuracymentioning
confidence: 99%
“…A heart rate-based apnea/hypopnea evaluation, a respiratory sound-based apnea/hypopnea evaluation, or a pulse attenuation evaluation for apnea/hypopnea events are surrogates. 6 Surrogates may serve very well against the reference standard and may do their job well in clinical practice. 6 For summing up these surrogates the term "respiratory disturbance index (RDI)" was coined, being different from AHI.…”
Section: Apnea Hypopnea Rdi Surrogatesmentioning
confidence: 99%
“…6 Surrogates may serve very well against the reference standard and may do their job well in clinical practice. 6 For summing up these surrogates the term "respiratory disturbance index (RDI)" was coined, being different from AHI. This opens our eyes to the problem that nasal prongs or thermal sensors provide surrogates for airfl ow as well.…”
Section: Apnea Hypopnea Rdi Surrogatesmentioning
confidence: 99%
“…32 This device is validated for the diagnosis of OSA. 22,[33][34][35][36] The PAT signal is a measure of sympathetic activity and is augmented, along with an increase in the heart rate and a decrease in oxygen saturation, at the termination of a respiratory event. 32,34 Using the above measurements, this device can indirectly detect respiratory events.…”
mentioning
confidence: 99%